Fuelwood use and availability in “La Montaña” region in the state of Guerrero and their implications in the environmental unity - Salgado Terrones, Omar; Borda Niño, Mónica Lorena; Ceccon, Eliane (Instituto de Ecología, A.C., 2017)
“La Montaña” region, in Guerrero state, in Southern Mexico, shows high poverty and deforestation rates. At the same time, the peasants show a high dependency on forests, particularly on timber use for fuelwood. The aim of this work was to characterize and quantify the use of fuelwood and determine its availability in the different landscape units across the study site. To estimate species utilized and preference for species, 60 households were surveyed in three localities at different altitudes. The quantity of fuelwood consumed was measured using two weight survey methods: Daily average and Direct consumption. To assess the fuelwood availability, the floristic composition and structure of the more preserved with minimum fuelwood extraction patches were determined and an extrapolation was made to cover the entire study site. It was found that the utilization process of the species is similar along the altitudinal gradient: all of households surveyed daily use fuelwood with an average per capita consumption of 1.70 kg and 2.06 kg (according to both survey methods) and 63% of the users perform the extraction of complete trees mainly from Quercus species. An availability of live biomass for fuelwood of 28 t ha-1 and 14 t ha-1 1 was found in patches of closed and open forest, respectively. Due to the similarities found, in terms of use and availability, it is possible to consider the different units studied as an environmental unity for the establishment of productive restoration projects.